Fabrication of ultraviolet/thermal-sensitive PMMA/PDMS wrinkle structures and the demonstration as smart optical diffusers. Issue 7 (1st April 2023) - Jiang, Shulan; Yin, Xiaolin; Bai, Jinxuan; Yu, Bingjun; Qian, Linmao
Abstract: Although smart optical diffusers have received increasing attention for the next generation of flexible optoelectronics, the exploration and fabrication of low-cost ultraviolet/thermal-sensitive optical diffusers are still challenging. In this study, we used a cost-effective method to fabricate flexible PMMA/PDMS wrinkle structures, demonstrating their applicability as tunable ultraviolet/thermal-sensitive optical diffusers. As the temperature gradually increased, the wrinkle wavelength changed slightly while the amplitude decreased. The wrinkle wavelength remained unchanged after UV light exposure, while the wrinkle amplitude decreased with the illumination time. When the fabricated structures were used as optical diffusers, the number of light diffraction pattern rings decreased with the wavelength of the wrinkle structures. Optical diffusers with different wrinkle patterns and the same aspect ratio exhibited different diffusing properties. The number of apertures and the coverage area of the diffused spot gradually decreased when the optical diffuser structure was exposed to heating. Remarkably, the optical diffusers could recover to their original state quickly after cooling. The number of apertures and the coverage area of the diffused spot gradually decreased with UV irradiation time. The prepared PMMA/PDMS wrinkle structures exhibit great potential for intelligent displays, wise medical systems, and other smart devices.